the length of a garden is 4 m longer than the width. if the area of the garden is 196m^2, find the width of the garden.

Answers

Answer 1
Answer: l = 4 + w 
w = w 
A = 196 m^2

A = lw
A= (4+w)w
196 = w^2 +4w

w^2 + 4w - 196 = 0

The quadratic roots (or zeros) of the function are 12 and -16. 

Since -16 does not make sense as a measure of width, then 12 is the answer. 



Related Questions

A small plane is 4 miles by land away from the airport. The angle of elevation from the airport to the airplane. What is the altitude of the plane? Round your answer to the nearest tenth of a mile.
Solve for x: 4 − (x + 2) < −3(x + 4)
What is the volume of the right prism? 5 cm 10 cm 6 cma.2250 cm3 b.1500 cm3 c.150 cm3 d.25 cm3
What this is square root of 164 divided by two
The lateral faces of a regular triangular prism are _____.isosceles triangles equilateral triangles parallelograms rectangles

Z is the circumcenter. What is VZ?

Answers

Answer:

VZ is 24

Step-by-step explanation:

when we talk of the circumcenter, we mean a point in the triangle that has a uniform distance from each of the vertices of the triangle

What we mean by the circumcenter is that the length between this point and any of the vertices is the same distance

ZU is a distance between the circumcenter and the vertice

What we want to calculate top is same.

So therefore, the two are equal and we have the length of what we want to

calculate as 24

What adds up to 12 but multiplies to 60

Answers

There is no possible combination that satisfy the given system of equations.

What is function?

A function is a relation between a dependent and independent variable.

Mathematically, we can write → y = f(x) = ax + b.

Given is to find what adds up to 12 but multiplies to 60.

We can write -

x + y = 12

xy = 60

Refer to the graph. The lines do not intersect. So, there is no possible combination that satisfy the given system of equations.

Therefore, there is no possible combination that satisfy the given system of equations.

To solve more questions on system of equations, visit the link-

brainly.com/question/29014197

#SPJ2

The answer is 6. Because, 6+6=12 and 6*10=60. Any more questions?

What two numbers multiply to 64 and add up to negative 16

Answers

The two numbers multiply to 64 and add up to negative 16 are -8, -8.

What is Algebraic expression ?

Algebraic expressions are numbers expressed using letters or alphabets without specifying their values. Algebra taught us how to express unknown values using letters such as x, y, and z. There can also be a single value that is placed before and multiplied by a variable in an algebraic expression in addition to these letters, which are called variables.

Let us assume first number be = x

and, let the second number be = y

then,

multiplication of two number will be :

xy = 64...(1)

addition of two numbers will be -16 that is :

x + y = -16..(2)

we have :

(x+y)² - (x-y)² = 4xy

(x-y)² = (x+y)² - 4xy

(x-y)² = (-16)² - 4 x 64

(x-y)² = 256 - 256

(x-y)² = 0

(x-y)  = 0

x = y

Now, from equation (2) we have ":

x + y = -16

x + x = -16

2x = -16

x = y= -8

Therefore, the two numbers multiply to 64 and add up to negative 16 are -8, -8.

more on algebraic expression at :

brainly.com/question/20660076

#SPJ2

well we have : ----- × ------ = 64 
                        -----+ ------- = -16  ⇒ so both of the numbers gonna be -8 
-8 × -8 = 64 and -8-8 = -16 :))) i hope this be helpful 

Which statement is true about the equation 3/4z = 1/4z − 3 + 5? It has no solution. It has one solution It has two solutions. It has infinitely many solutions.

Answers

A linear equation is known to have quite of 1 solution
(3)/(4)z = (1)/(4) z - 3 + 5

solve for the value(s) of z
(3)/(4)z -  (1)/(4) z = 2 <span>
(z)/(2) = 2
z = (2)/(2)
z = 1 

Witch expression has the same value as 2 to the power of 12

Answers

Answer:

4096

Step-by-step explanation:

2^12

=2x2x2x2x2x2x2x2x2x2x2x2=4096

Please look at this multiple choice. thanks!!!!

Answers

Step-by-step explanation:

y =  - 2x + 3

The slope of the above line = -2

slope of the line perpendicular to the above line = 1/2

If it passes through point (4,-3) , it's equation

(y - ( - 3))/(x - 4)  =  (1)/(2)

(y + 3)/(x - 4)  =  (1)/(2)

2(y + 3) =  x - 4

2y + 6 = x - 4

x - 4 - 2y - 6 = 0

x - 2y - 10 = 0

A = 1, B = -2 and C = -10

A+B+C= 1+(-2)+(-10)

= 1-2-10

= 1-12

= -11

Answer:

A = 1, B = -2 and C = -10

Step-by-step explanation: